To evaluate the effectiveness of a structured teaching program on Management of Premenstrual Syndrome for high school girls aged between 12 to 15 years in a selected High school, Hyderabad - Yadav, Seema; Joyce, (International Journal of Psychosocial Rehabilitation, 2020)
Objectives of the study were:➢ To assess the knowledge level of the adolescent girls regarding management of premenstrual syndrome by pretest.➢ To develop and administer a structured teaching program on management of premenstrual syndrome to the high school girls.➢ To assess the effectiveness of a structured teaching program through post-test.➢ To determine the association between knowledge and selected biosociodemographic variables.The study adopted the pre-experimental one-group pre-test post-test design with the structured teaching as the independent variable and knowledge of management of premenstrual syndrome by the high school girls aged between 12 and 15 years as the dependent variable. The population of the study was the high school girls studying in classes from Std. VII to Std. X, aged between 12 and 15 years. The size of the sample was fifty.The data was collected by the interview method with the help of a structured questionnaire. The reliability of the questionnaire was assessed by using the split-half method. The correlation coefficient was calculated using Karl Pearson's formula, and the reliability R of the structured questionnaire is found to be practical.It was observed that before the structured teaching program, 100% of the schoolchildren were below average regarding the knowledge of management of premenstrual syndrome, and no schoolchildren were above average or even in the average category. The overall performance of the pre-test mean score was 10.14 (25.35%), whereas the overall post-test mean score was found to be 23.06 (57.55%). The tabulated paired 't' test was 16.82, which is very much higher than the tabulated 't' value of 2.3124 at 49 degrees of freedom with a 5% level of significance. The data shows that there was a significant difference in the overall pre-test and post-test knowledge scores among high school girls. Hence the first formulated hypothesis was accepted. The chi-square test for assessing the association between knowledge scores of the high school girls and selected bio-sociodemographic variables shows that the knowledge scores are associated with the occupation of the subject's father. Remaining all selected bio-demographic variables have no association with the knowledge scores. The findings show that the knowledge of the management of premenstrual syndrome can be improved with a structured teaching program and help them to lead a healthy reproductive life.